A new composite electrode applied for studying the electrochemistry of insoluble particles: α-HgS - Yang, M; Compton, R (Wiley, 2018)
The redox chemistry of solid α-HgS particles is revealed using a carbon/PVDF composite containing α-HgS, carbon black, polyvinylidene fluoride (PVDF). The electrochemical behaviour of the carbon/PVDF composite is first characterised with three water insoluble organic solids. Then the reduction of solid α-HgS particles is investigated and found to occur at a high negative potential, -1.82V vs saturated mercury sulphate reference electrode, to form metallic mercury and sulphide ions. The subsequent oxidation of metallic mercury and sulphide occurs at +0.24V and -0.49V vs MSE respectively.